ILMU URFON, WHO ROSE UNDER THE TIMURIDS, SPIRITUAL AND ENLIGHTENED VIEWS - Salamov Khurshid Bariddinovich (American Journals, 2024)
This article examines the fundamental changes in the socio-economic, political, cultural, spiritual, and educational life of the peoples of Central Asia in the late 14th and 15th centuries, the rise of advanced knowledge and science during the Timurid period. The works of Alisher Navoi analyze science, the culture of Mirzo Ulugbek, and Alisher Navoi's contribution to the development of well-being, such qualities as morality and spiritual maturity.
Keywords: Patriotism, spirituality, enlightenment, renaissance, humanity, equality, justice, enlightenment.